The Bond between Psychoanalysis, Education, Cinema and Adolescent Experience - Rose Gurski; Jane Fischer Barros; Stéphanie Strzykalski (Universidade Federal do Rio Grande do Sul, 2019)
In this article, we reflect on some methodological effects for the intervention research with adolescents that come from the encounter between Psychoanalysis, Education and Cinema. In order to do that, we start from the experience Cine na Escola. It is a device through which we offer cinema sessions with the opening of a space for the circulation of words to the adolescents of a public school, located in a region with high rates of violence and vulnerability in our city. Articulating the discussion with Giorgio Agamben's concept of profanation, we propose to profane the utilitarian use of the cinema, evoking the dimension of the new in the adolescent passage.